Near net-shape fabrication and properties of graphitic carbon foam with a continuous network of graphite nanosheets. Issue 12 (15th June 2022) - Zhou, Yunhong; Guo, Yiyou; Wu, Renquan; Wang, Zhuqi; Liu, Yifei; Lin, Qilang
Abstract: A near net-shape graphitic carbon foam (GCF) with a continuous network of graphite nanosheets was prepared by direct carbonization of epoxy resin filled with nano-Al2 O3 . The effects of carbonization temperature on the properties of the resulting carbon foams were investigated by SEM, TEM, XRD, Raman, thermal conductivity and compression strength test. The results show that the as-prepared GCF can maintain well dimensional stability upon carbonization. The carbothermal reaction between the nano-Al2 O3 and carbon foam matrix greatly influences the microstructure of carbon foam and promotes its growth of the continuous network of graphite nanosheets. In addition, the GCF prepared at 1700 °C possesses a compressive strength of 2.34 MPa with a bulk density of 0.19 g cm -3, and meanwhile presents a high graphitization degree of 65.12% and a thermal conductivity of 2.02 W/mK. The continuous network of graphite nanosheets favors the enhancement of thermal conductivity of carbon foam and simultaneously prevents the decline of compressive strength further.